Effect of low body mass index on clinical recovery after fusion surgery for osteoporotic vertebral fracture: A retrospective, multicenter study of 237 cases. Issue 52 (30th December 2022) - Inoue, Gen; Miyagi, Masayuki; Saito, Wataru; Shirasawa, Eiki; Uchida, Kentaro; Hosogane, Naobumi; Watanabe, Kei; Katsumi, Keiichi; Kaito, Takashi; Yamashita, Tomoya; Fujiwara, Hiroyasu; Nagamoto, Yukitaka; et al.
Abstract : A retrospective multicenter study. Body mass index (BMI) is recognized as an important determinant of osteoporosis and spinal postoperative outcomes; however, the specific impact of BMI on surgery for osteoporotic vertebral fractures (OVFs) remains inconclusive. This retrospective multicenter study investigated the impact of BMI on clinical outcomes following fusion surgery for OVFs. 237 OVF patients (mean age, 74.3 years; 48 men and 189 women) with neurological symptoms who underwent spinal fusion were included in this study. Patients were grouped by World Health Organization BMI categories: low BMI (<18.5 kg/m 2 ), normal BMI (≥18.5 and <25 kg/m 2 ), and high BMI (≥25 kg/m 2 ). Patients' backgrounds, surgical method, radiological findings, pain measurements, activities of daily living (ADL), and postoperative complications were compared after a mean follow-up period of 4 years. As results, the proportion of patients able to walk independently was significantly smaller in the low BMI group (75.0%) compared with the normal BMI group (89.9%; P  = .01) and the high BMI group (94.3%; P  = .04). Improvement in the visual analogue scale for leg pain was significantly less in the low BMI group than the high BMI group (26.7 vs 42.8 mm; P  = .046). Radiological evaluation, the Frankel classification, and postoperative complications were not significantly different among all 3 groups. Improvement of pain intensity and ADL in the high BMI group was equivalent or non-significantly better for some outcome measures compared with the normal BMI group. Leg pain and independent walking ability after fusion surgery for patients with OVFs improved less in the low versus the high BMI group. Surgeons may want to carefully evaluate at risk low BMI patients before fusion surgery for OVF because poor clinical results may occur.